Islam Nusantara as Strategy for Indonesian Nasionalism Inauguration - Badrun, Badrun (LPPM IAIN Kudus, 2019)
The discourse on Islam Nusantara has become quite popular discussion among Indonesian society in the last two to three years. Not only in the grassroots level, Islam Nusantara also becomes a study in several Islamic institutions in Indonesia. In fact, there are some Islamic universities that have opened Islam Nusantara study program. On the one hand, many groups welcomed the studies of Islam Nusantara after being proclaimed by Nahdliyyin in the 33th NU Congress in Jombang, 2015. But on the other hand, there are some groups who reject Islam Nusantara and considered it as heresy in Islam. Essentially, Islam Nusantara is not a new movement, not a new mazhab, not a new ideology, and certainly not a new religion. Islam Nusantara is Islam that exists in the nation and is not sourced from the nation. However, Islam Nusantara accepts and accommodates national cultures as long as it does not contradict the Islamic rules (sharia). It means, Islam Nusantara compromises the culture, appreciates the land where they live, but it does not eliminate tradition as long as it is still in harmony with Islamic sharia. This can become the foundation of our nationalism inauguration. In other words, Islam Nusantara does not only discuss about religious issues, but also about nationalism.